Practical Aspects of Computational Chemistry IV - Leszczynski, Jerzy; Shukla, Manoj K. (Springer US : Imprint: Springer, 2016)
The editors of this volume have compiled an important book that is a useful vehicle for important computational research - in the development of theoretical methodologies and their practical applications. Themes include new methodologies, state-of-the-art computational algorithms and hardware as well as new applications. This volume, Practical Aspects of Computational Chemistry IV, is part of a continuous effort by the editors to document recent progress made by eminent researchers. Most of these chapters have been collected from invited speakers from the annual international meeting: "Current Trends in Computational Chemistry" organized by Jerzy Leszczynski, one of the editors of the current volume. This conference series has become an exciting platform for eminent Theoretical/Computational Chemists to discuss their recent findings and is regularly honored by the presence of Nobel laureates. Certainly, it is not possible to cover all topics related to the Computational Chemistry in a single volume but we hope that the recent contributions in the latest volume of this collection adequately highlight this important scientific area.